PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR SISWA UPTD SDN 3 JUNTIKEDOKAN - Amanaturrakhmah, Isna (Jurnal Tawadhu, 2020)
This research is motivated by the ineffectiveness of the learning process in learning Theme 1 Growth and Development of Living Things Subtheme 1 Characteristic of Living Things which caused low learning outcomes and the KKM has not been achieved. The research method used is Classroom Action Research (CAR) carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The target of this research is class III, techniques in data collection include observation and evaluation tests. Evaluation tests are carried out at the end of each cycle. The results showed that the application of the Snowball Throwing learning model could improve student learning outcomes in learning the theme 1 growth and development of living things subtheme 1 characteristics of living things. This is evidenced by an increase in student learning outcomes in each cycle. in the initial conditions before being given the action there were only 7 out of 32 students who completed the KKM. In the first cycle there was an increase, 18 out of 32 students completed the KKM. In the second cycle there was a significant increase, 29 out of 32 students completed the KKM. Thus it can be said that the application of the Snowball Throwing model can improve the learning outcomes of third-grade students at UPTD SDN 3 Juntikedokan.